Branding the Berries: Consumers’ Strawberry Purchasing Intent and their Attitude toward Florida Strawberries - Taylor K. Ruth; Joy N. Rumble (Journal of Applied Communications, 2016)
Florida is the largest producer of strawberries in the United States during the winter months. Recently, Florida has faced competition from strawberries imported from Mexico during peak season. Studies have shown that using state branding can help promote local produce. Branding can create perceived differences between identical items, as well as strong positive associations with the product. This study examined consumers' strawberry purchasing intent and attitudes toward Florida strawberries to aid agricultural communicators in creating effective communication and branding strategies. An online survey was distributed throughout Florida (n = 500). Results indicated that freshness and taste were the most important qualities of strawberries for purchasing decisions and that Florida strawberries were viewed more positively than Mexico strawberries. When respondents were given the option between labels with and without a Fresh from Florida brand logo, the majority preferred to purchase the package labeled Fresh from Florida. Consumers with a lower income were less likely to purchase state branded strawberries. Gender did not have an impact on purchasing intent for strawberries. Using the Fresh from Florida brand for Florida strawberries was a key recommendation from this study, along with using sensory words, like taste and freshness, when marketing strawberries. Also, developing outreach programs to inform lower- income families when produce is in season will help promote the sale of local products. These recommendations could be expanded to other states and commodities.
Keywords: Branding; Competition; Imports; Local; Locally Grown; Strawberries